Stratigraphy and Structure of the Southeastern Cape Breton Highlands, Nova Scotia - Raeside, Robert; Barr, Sandra (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1986)
The southeastern Cape Breton Highland** are composed of an eastern belt of predominantly granitoid rocks and a western belt of dloritic, granitoid and stratified rocks. The oldest unit is Inferred to be the Chetlcamp Lake gneiss, which outcrops in the western belt. This is in faulted contact with the most extensive stratlgraphic unit. the McMillan Flowage Formation, which occurs throughout the western belt. It represents early Paleozoic or older continental nwrg-fn accumulations of sandy and silty clastic sedimentary, volcanic, volcaniclastic and rare calcareous rocks. These stratified units have been folded and Intruded by late Precambrian(?) to lower Paleozoic granitoid and dloritic plutons. and then have undergone a later strike-slip deforma-tional event. In the eastern belt, the Baracbois River unit preserves a section of siltstones and greywackes which have been largely metamorphosed to gneisses, and the Price Point unit includes a small section of volcanic rocks. A single pervasive foliation has been recognized in the eastern belt. The two belts appear to represent components of two tectonostratigraphic zones, the western belt being part of the Highlands zone, and the eastern belt part of the Bras d'Qr zone of Cape Breton Island. The western belt displays a pronounced Devonian thermal overprint, whereas the eastern belt has preserved late Precambrian or Siluro-Qrdoviclan ages. Neither belt can readily be correlated with the Southeastern zone of Cape Breton Island or the Avalon Zone in Newfoundland. Based on lithologic similarities. both In the stratified units and in the nature of the plutonic rocks, the western belt (Highlands zone) can be correlated with the Gander zone. The eastern belt (Bras d'Qr zone) is a possible manifestation of the Avalon zone at a deeper crustal level.